Performance Evaluation of Thermal Enhanced Oil Recovery by In-situ Combustion - Sairam, D; Reshma, G; P, Arjun; Deepu, Y (International Journal of Engineering and Technology, 2018)
Thermal methods of enhanced oil recovery and especially the in-situ combustion known to the efficient methods among the known enhanced oil recovery methods. In this method heat is added to the reservoir to reduce the oil viscosity. So, that it can be more efficiently driven to the producing well. However the experimental analysis of ISC to understand its operation is known to be expensive. Therefore we have developed a 1D model using STARS module of CMG where in we have Cartesian grid. To this we have given and given i, j, k values. Later porosity, Temperature and initial pressures are given. For setting the well we have used injector and producer. After checking errors we have validated the model. It is evident from the performance plots that the temperature along the core is a function of the gas injected and the oil saturation. However the as the temperature moves along the reservoir from injection well the oil saturation is observed to decrease in the vicinity of the well and start to build away from the injection well towards the production well. This is work provides a platform to understands the combustion propagation and its role in improving the oil recoveriesÂ Â